2005
DOI: 10.1385/ncc:2:1:043
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Surge Precedes Intracerebral Hemorrhage

Abstract: In this monitored case, the BP surge clearly preceded the onset of neurological symptoms by 3.5 hours, supporting the view that the acute BP elevation was the cause of ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Several investigators have proposed that an exaggerated morning BP surge may advance vascular remodeling from the larger arteries to the small resistance vessel because of the shear stress of an exaggerated fluctuations of blood flow on the vessel wall. [22][23][24] Indeed, various cardiovascular morbidities have been described in patients with an exaggerated morning BP surge. These studies, conducted primarily in adults, consistently indicate that morning BP surge is an important predictor of the development of risk markers such as increased carotid intima thickness 14 myocardial hypertrophy and infarction 25 and cardiovascular events, such as stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have proposed that an exaggerated morning BP surge may advance vascular remodeling from the larger arteries to the small resistance vessel because of the shear stress of an exaggerated fluctuations of blood flow on the vessel wall. [22][23][24] Indeed, various cardiovascular morbidities have been described in patients with an exaggerated morning BP surge. These studies, conducted primarily in adults, consistently indicate that morning BP surge is an important predictor of the development of risk markers such as increased carotid intima thickness 14 myocardial hypertrophy and infarction 25 and cardiovascular events, such as stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute BP elevations were suggested as contributing to the cause of the ICHs in these cases, BP monitoring prior to and at the onset of the ICH was unavailable. Leira et al have reported the case of a neurologically intact 64-year-old female who was monitored in an ICU for respiratory distress and subsequently became altered, exhibiting a right hemispheric syndrome 3.5 h after developing SBP in the 200 mmHg range [10]. An unenhanced CT of the brain subsequently demonstrated a right ICH.…”
Section: Discussionmentioning
confidence: 99%
“…We itere Risikofaktoren für eine primäre ICB sind einerhöhtesLebensalter(mit einer Ve rdopplung desR isikos etwa alle 10 Jahre), männlichesG eschlecht ( Unabhängige Faktoren in derAkutphase derICB,die sich ungünstigauf denVerlauf auswirken,s ind eine erhöhte Körpertemperatur von>3 7,5°C, eine Erhöhung des Blutglukosespiegels, eine rhöhterF ibrin-spiegelimSerum von>523 mg/dl sowieein noch nach 48 Stundene rhöhterB lutdruck (33,34,47).…”
Section: äTiologieund Risikofaktorenunclassified